More fruit diversity for food security - Carpentier, Sebastien; Machida, Lewis; Tazuba, Anthony Fredrick; Van Gils, Daan (2024)
Banana (Matooke) is a staple crop in Uganda and the east and central African region (Tanzania, Rwanda, Burundi, Kenya, and Democratic Republic of Congo). Climate change is expected to increase the growing area of bananas in general but for Matooke this is expected to decrease due to the increased evaporative demand. To avert climate change and drought-induced food shortages and hunger in the Matooke growing areas, mapping the current banana diversity in function of the environment is, therefore, urgently needed to give matooke farmers more cultivar options for improved on farm diversity and resilience to climate change. More than 1600 germplasm accessions kept at the International Transit Centre are currently available for this mapping exercise. Strengthening of collaboration with partners is currently going on, with NARO, TARI and IITA endorsing the need for the mapping exercise for the benefit of breeding programs. A proof of principle of diversity funded by the Belgian Development Cooperation has been delivered but we need more resources to scale up jointly with NARO, TARI and IITA for the benefit of farmers in different agro-eco zones of the East African Great Lakes region